Cloud Computing Security Concepts and Practice - Harkut, Dinesh G. (IntechOpen, 2020)
Cloud computing is an emerging discipline that is changing the way corporate computing is and will be done in the future. Cloud computing is demonstrating its potential to transform the way IT-based services are delivered to organisations. There is little, if any, argument about the clear advantages of the cloud and its adoption can and will create substantial business benefits through reduced capital expenditure and increased business agility. However, there is one overwhelming question that is still hindering the adaption of the cloud: Is cloud computing secure? The most simple answer could be 'Yes', if one approaches the cloud in the right way with the correct checks and balances to ensure all necessary security and risk management measures are covered as the consequences of getting your cloud security strategy wrong could be more serious and may severely damage the reputation of organisations.